(untitled) (Tidsskrift for Praktisk Teologi, 2020)
This article discusses how aspects of anomalous experiences can be understood in theology andpsychology and investigates the premises on which dialogues between the two disciplines may faci-litate more nuanced interpretations of such experiences. Two key issues are focused on: how ano-malous experiences can be interpreted as religious experiences, and how they are connected tomental health. By relating empirical studies of anomalous experiences to interdisciplinary theoreti-cal reflections, it is argued that there is a potential in the dialogue to buffer reductionist tendenciesin the two, separate disciplines. Holding a repertoire of different interpretations on these issues isfurther considered to be beneficial in professional practice when encountering people with anoma-lous experiences.